PERAN PEMERINTAH JAWA BARAT DALAM PEREKONOMIAN DI JAWA BARAT PADA MASA PANDEMI COVID-19 - Berry Natanael Montana (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2023)
This paper aims to analyze the role of the West Java government in efforts to grow the economy during the Covid-19 pandemic. There are 9 priorities from the West Java government policy, namely 1) Decentralization of health services; 2) Economic organization based on innovation; 3) Access to education; 4) Religious education; 5) Development of infrastructure and tourist destinations; 6) Building movement of the village; 7) Regional connectivity; 8) Regional structuring innovation and public services; 9) Subsidies for economically weak groups. Government policies are analyzed by looking at the realization of the implementation of government policies that occur in the field. The data was obtained from the RKPD which was presented at the West Java BAPPEDA event by looking at the alignment between government policies and practices that occur in the field.